Urban transportation planning in the United States : an historical overview - Weiner, Edward (Praeger, 1999)
This work describes the evolution of urban transportation planning from its beginnings in early highway and transit planning to late-1990s concerns for the environment and sustainable development. The author discusses the influence of legislation, regulations and federal programmes.
Keywords: Urban transportation policy -- United States -- History.; Transports urbains -- Politique gouvernementale -- États-Unis -- Histoire.; TRANSPORTATION -- Public Transportation.; Urban transportation policy; United States; Lokaal verkeer.; Lokaal vervoer.; Stadsplanning.; Urban transportation policy -- United States.; Urban transportation -- United States -- Planning.; History